Unanticipated Shocks and Systemic Influences : The Impact of Contagion in Global Equity Markets in 1998 - Gonzalez-Hermosillo, Brenda (IMF Working Papers; Working Paper ;, 2003)
August to September 1998 has been characterized as one of the worst episodes of global financial distress in decades. This paper investigates the transmission of the Russian and the LTCM crises through global equity markets using a panel of 14 developing and industrial countries. The results show that contagion was systemic during the period, with industrial countries providing the dominant cross-country transmission linkages. Both crises reinforced each other, highlighting the importance of studying them jointly. An implication of the empirical results is that models of contagion that exclude industrial countries are potentially misspecified and may yield misleading outcomes.